Effects of temperature, salinity and diet on embryonic and early larval development in Littorina littorea (Gastropoda: Littorinimorpha) - Lillebjerka, Tora; Malzahn, Arne M.; Kjørsvik, Elin; Hagemann, Andreas (Frontiers in Marine Science, 2023)
Introduction The common periwinkle Littorina littorea is a delicacy in southern Europe. Enabling aquaculture production would be measure to avoid future over-harvesting and ensure a constant market supply. Methods However, knowledge gaps in reproductive biology needs to be filled to allow setting up rearing protocols. Results We investigated effects of temperature and salinity on embryonic development by incubating eggs at ten different temperatures in steps every 2°C, form 5 to 23°C) and four salinities (20 – 40). Embryonic development was clearly temperature dependent; eggs hatched after three days at the highest temperature while it took 16 days to hatch at the lowest temperature. Calculating effective day-degrees (DDeff) allowed expressing the thermal history of the embryogenesis and concluding that this species hatches on average at 61 (SD 3.7) DDeff. Larval growth- and developmental rates showed a different response to the temperature extremes as snails with the smallest shell lengths at hatch were found for the highest and lowest temperatures (204.5, SD = 11.6, and 202.9µm, SD = 13.7 respectively). Viable larvae only hatched at temperatures above 9°C. Larvae hatched at lower temperatures did not develop a shell or swimming lobes. Salinity and temperature significantly influenced time-to-hatch and hatching success; the lowest salinity (20PSU) lead to later hatching (80-100DDeff) and lower hatching success compared to higher salinities (25, 30, and 40, hatch around 40-50 DDeff). Neither hatch rate nor time-to-hatch showed differences among the higher salinities, suggesting a salinity threshold below 25. There was no significant interaction between salinity and temperature on time-to-hatch or hatching success. Larval diet had a significant effect on growth rates during the planktonic stage. Veliger larvae fed on two different live microalgae mono-diets (Dunaliella tertiolecta and Rhodomonas baltica) successfully passed their pelagic phase at the same time with no differences in growth rates, while veliger larvae fed on either of two preserved microalgae products (Nannochloropis sp. and Tetrasemis sp. frozen pastes) were not growing. Discussion We conclude that embryonal development can be successfully completed at temperatures between 7 and 20°C, while lower or higher temperatures should be avoided. Successfully hatched larvae can be fed on mono-microalgae diets until settlement.